Kaji Eksperimental Sifat Mekanik Honeycomb Sandwich Komposit Serat Karbon dengan Uji Bending - Marsono Marsono; Nuha Desi Anggraeni; Fajar Ahmad Faisal (Department of Mechanical Engineering, Universitas Andalas, 2021)
A higher energy efficiency in a high efficient energy car can be reached by using a honeycomb sandwich structure that is made from fiber-carbon composite which is lighter in weight. With a lighter weight, a higher power-to-weight ratio can be reached. In this research, honeycomb sandwich panels are made from fiber-carbon composite and tested to determine their flexural strength and stiffness. These honeycomb sandwich panels are made with varying thickness of core cell wall, which are made by 1 layer and 2 layers of fiber-carbon sheet. Matrix that is used is epoxy resin that is prepared in two methods, with and without heating. The bending test result shows that the highest flexural strength that can be reached is 5.193 kgf/mm2 which is reached by the specimen that has 2 layers’ fiber carbon with heating epoxy resin. Flexural stiffness is also reached by the same specimen, of 67.49 kgf/mm.